Pengaruh Model Teaching Games for Understanding terhadap Keterampilan Sosial dan Berpikir Kritis: Systematic Literature Review - Nida Indah Hayati; Tite Juliantine; Sucipto Sucipto (Jurnal Sporta Saintika, 2025)
This study aims to systematically examine the effect of the Teaching Games for Understanding (TGfU) model on social skills and critical thinking abilities in Volleyball extracurricular activities. The research employed a Systematic Literature Review (SLR) method consisting of planning, conducting, and reporting stages. Literature was collected from Google Scholar, Publish or Perish, Scopus, and ERIC databases covering publications from 2014–2024. The PRISMA selection process resulted in 12 eligible articles. The synthesis findings indicate that TGfU consistently improves students’ social skills, including communication, teamwork, empathy, and responsibility through tactical discussions and collaborative game situations. Furthermore, TGfU contributes to the development of critical thinking skills through game analysis, decision-making processes, and reflective tactical discussions. Several studies also reveal gender-based differences in responses to the implementation of TGfU. Overall, TGfU is an effective pedagogical approach for enhancing both social and cognitive development in Volleyball extracurricular contexts.